Microbiological Quality of Dried Bombay Duck (Harpodon Nehereus) Samples Obtained from North-Eastern Bangladesh (Sylhet District): Microbiological Quality of Dried Bombay Duck (Journal of the Asiatic Society of Bangladesh, Science, 2025)
This research was selected to assess the microbial and sensory quality of dried Bombay duck (loitta) in Sylhet district. Fourty eight (48) samples of dried Bombay duck (loitta) were collected from eight Upazila dried fish markets in Sylhet district in each of the eight upazilas during September 2022 to February 2023, the study collected 48 samples from two markets in each of the eight upazilas. Microbiological analyses included Aerobic Plate Count (APC), Total Coliform Count (TCC), presence of Escherichia coli & Salmonella spp., and sensory evaluation. Results revealed that aerobic plate counts showed the highest (log 5.69 ± 0.2) in Gowainghat upazila markets and the lowest (log 3.453 ± 0.2) in Sylhet sadar market. Total Coliform counts (ranged from 21 ± 1 to 80 ± 3 MPN/g) of the samples analyzed remained within permissible limits. The prevalence of Escherichia coli was found the highest in Gowainghat (67%) and the lowest in Sylhet Sadar and South Surma (17%), and the prevalence of Salmonella spp. was found the highest in Companiganj and Fenchuganj (67%) and the lowest in Sylhet Sadar (17%). Sensory examination favored samples from South Surma. Presence of pathogenic bacteria suggests unsanitary processing conditions. Dried fish quality varied significantly among upazilas, emphasizing the need for improved hygiene and sanitation practices to ensure safe, high-quality dried loitta production.J. Asiat. Soc. Bangladesh, Sci. 50(1-2): 101-111, June-December 2024